7 Tesla MRI with RF Power and Field Homogeneity Comparable to 4 Tesla using Computational Electromagnetics - Tang, L.; Ibrahim, T. S. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In ultrahigh (≥ 7 Tesla) field magnetic resonance imaging (MRI), the electromagnetic interactions between the coil, its excitation sources, and the biological load become more significant compared to low MRI applications. Computational electromagnetic (CEM) techniques are currently playing a major role in the evaluation of MRI radiofrequency (RF) coils (commonly now, within ultrahigh field context, referred to as transmit arrays). This work compares the RF power requirements in 4 and 7 Tesla human MRI using CEM. Furthermore, we demonstrate that at ultrahigh MRI, highquality/ homogenous RF excitation fields could be obtained simultaneously with total RF power deposition lower than that achieved at lower field strengths. These results dispel what has been widely accepted from quasistatic approximations, namely that pushing the envelope of MRI field strength results in more RF power requirements and therefore, more RF power absorption in human tissue. This study is presented using the finite difference time domain (FDTD) method and a gradient based optimization method.